Political Fund ballot - union poster, 1985 (London, 1985)
1985 1980-95 "Political Fund ballot - union poster, 1985" [BW0181], 1985, Trades Union Congress The Trade Union Act 1984 required trade unions to ballot their members every ten years for approval to continue to operate their respective political funds. The Bakers, Food and Allied Workers Union produced this poster as part of its 1985 ballot campaign.